1997
DOI: 10.1159/000127224
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Inhibit Stress-Induced Phosphorylation of CREB in Corticotropin-Releasing Hormone Neurons of the Hypothalamic Paraventricular Nucleus

Abstract: The corticotropin-releasing hormone (CRH) gene contains a perfect palindromic motif in its promoter region that allows binding of the cyclic adenosine monophosphate response element binding protein, CREB. Since previous studies suggest that the CRH gene can be activated by cyclic adenosine mono-phosphate, we determined whether stress and feedback inhibition by glucocorticoids in CRH-producing neurons in the hypothalamic paraventricular nucleus could be mediated by changes in the phosphorylation of CREB. Antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 28 publications
6
26
1
Order By: Relevance
“…In line with our previous data, a cAMP/PKA pathway activator, forskolin, about three-fold enhanced CRH-CAT activity in differentiated Neuro-2A cells (Budziszewska et al, 2004), while in another cell line a much larger increase was observed (Seasholtz et al, 1988). Furthermore, it has been found that stress-induced CRH synthesis in the hypothalamic neurons is most probably evoked by cAMP-PKA pathway activation, and in consequence the increased phosphorylation of CREB (Legradi et al, 1997). Since forskolin-stimulated CRH activity was inhibited by clozapine, chlorpromazine, haloperidol, and thioridazine, it can be expected that these drugs should also inhibit stress-stimulated CRH synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our previous data, a cAMP/PKA pathway activator, forskolin, about three-fold enhanced CRH-CAT activity in differentiated Neuro-2A cells (Budziszewska et al, 2004), while in another cell line a much larger increase was observed (Seasholtz et al, 1988). Furthermore, it has been found that stress-induced CRH synthesis in the hypothalamic neurons is most probably evoked by cAMP-PKA pathway activation, and in consequence the increased phosphorylation of CREB (Legradi et al, 1997). Since forskolin-stimulated CRH activity was inhibited by clozapine, chlorpromazine, haloperidol, and thioridazine, it can be expected that these drugs should also inhibit stress-stimulated CRH synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…GR prevents CREB phosphorylation by direct linking to the protein and hindering its binding to CRE. In addition, glucocorticoids can directly affect CREB function by interfering with the phosphorylation of CREB (Legradi et al 1997). A significant difference in GR number and function in various cerebral areas characterize the transgenic mice used in this study, in the absence of significant elevations in peripheral corticosterone.…”
Section: Discussionmentioning
confidence: 97%
“…52 There are cAMP-response elements located in the CRF gene promoter and binding of CREB stimulates CRF gene expression. 27 In vitro, glucocorticoids inhibit the CRF promoter through cAMP-dependent activity. 53 However, in our study, a change in CREB mRNA to accompany the increase of CRF mRNA expression in the PVN in depression was not found, so that our data do not provide support for a central role of CREB in the PVN in mood disorders.…”
Section: Crf Neurons and Crfr1 And Crfr2 Imbalancementioning
confidence: 99%
“…Alternatively, CRF gene regulation by CREB might not be attributed to different expression levels of CREB mRNA but to protein levels of phosphorylated CREB, which has been studied both in vitro and in vivo. 27,54 GR and MR imbalance The glucocorticoid feedback on the HPA axis is mediated by two types of receptors, GR and MR that have a different localization in the brain. 16 In depression, a downregulation of these receptors, secondary to the persistent hypercortisolism was presumed.…”
Section: Crf Neurons and Crfr1 And Crfr2 Imbalancementioning
confidence: 99%